A meta-analysis of income and democracy. Issue 2 (17th February 2018) - Broderstad, Troy Saghaug
ABSTRACT: The purpose of this article is to examine the relationship between per capita income and democracy. Namely, do increases in income per capita affect a regime's level of democracy? The scholarly tradition has investigated this question over many years, and what we have learned about the actual association between these variables remains inconclusive. As opposed to producing yet another empirical analysis of this hypothesized relationship, this article sets forth to examine it via a new methodological approach. Applying the tools of meta-regression analysis to 33 individual empirical studies that investigate the relationship between income and democracy, this article finds that income has no statistically significant, quantitatively meaningful effect on democracy (understanding the latter as a graded concept). I also show that there is no theoretical or empirical reason to believe that this field of research is "haunted" by publication selection bias. Moreover, I identify a variety of systematic differences between these studies, that is, study heterogeneity, which explain why it is the case that after 60 years of research we still have not reached a consensus.